Die Censor as Handhawer of Bewaker van Moreel-goeie Handelinge: Voorganger vir die Openbare Beskermer - Swartz, N. P. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2009)
The question quis custodiet ipsos custodes was asked centuries ago in the Roman Empire by the satirist, Juvenal. It means literally “who watches the watchmen?” or “who guards the guards?” In addition, it points to the promotion of the maintenance of moral good acts among the citizens, also those persons who must defend the rights and interests of the individual against the abuse of power by persons who possess public authority. The duties of the then censor shows tangencies with that of the present-day public protector. In this article it will be displayed whether or not the public protector has continued the duties and abilities of the censor. If it is evident that the censor was indeed the predecessor for the public protector, then it is necessary to reveal the phases it underwent to culminate eventually in the public protector. At times the duties and abilities of the censor had to undergo development or changes to conform to the changing circumstances of the time. Notwithstanding such developments or changes, the maintenance of moral good acts had remained the same for both offices and this is particularly the purview of this article.